The east China Sea ADIZ : new flashpoint in regional maritime security - Yoon, Sukjoon (2014)
Regional maritime territorial disputes have expanded beyond the surface of the seas into the airspace above them, marking a significant enlargement of the theatre of conflict. Why has China established the East China Sea (ECS) Air Defence Identification Zone (ADIZ)?